Quality of agile adoption in global software development: An assessment model - Mahnaz Afshari; Taghi Javdani Gandomani (Institute of Advanced Engineering and Science, 2021)
Over the last decade, software development has faced two approaches to Agile and global software development (GSD). While Agile development is focused on the reduction of software development overhead by reducing the distance between individuals and face-to-face communications, in global software development, the use of human power in various sites is considered. Despite their inherent differences, the combination of these two approaches has received considerable attention from researchers and software professionals. Meanwhile, the lack of a model or tool capable of assessing teams' adaptation to Agile methods seems to be a research gap. The current research aims to solve this challenge by proposing a model in this regard. Considering the major related factors and weighting them, this model allows software teams to assess the rate of their adaptation and success in global software development.